2019
DOI: 10.1155/2019/4596150
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of the Dental Stem Cell Secretome on Nerve Regeneration: Towards Cell-Free Treatment

Abstract: Cell-free treatment is emerging as an alternative to cell delivery to promote endogenous regeneration using cell-derived factors. The purpose of this article was to systematically review studies of the effects of the dental stem cell secretome on nerve regeneration. PubMed and Scopus databases were used where searched and related studies were selected. The primary search identified 36 articles with the utilized keywords; however, only 13 articles met the defined inclusion criteria. Eight out of thirteen articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 74 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…For example, hDPSCs showed a higher suppression rate of T lymphocyte growth [ 12 , 38 ]. hDPSCs and SHEDs revealed a higher trophic factor expression compared to BMMSCs [ 12 , 35 , 53 ]. Finally, hDPSCs and SHEDs are considered MSCs, because they fulfill the standard ISCT requirements to define a cell type as MSCs [ 29 , 30 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, hDPSCs showed a higher suppression rate of T lymphocyte growth [ 12 , 38 ]. hDPSCs and SHEDs revealed a higher trophic factor expression compared to BMMSCs [ 12 , 35 , 53 ]. Finally, hDPSCs and SHEDs are considered MSCs, because they fulfill the standard ISCT requirements to define a cell type as MSCs [ 29 , 30 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Finally, hDPSCs and SHEDs are considered MSCs, because they fulfill the standard ISCT requirements to define a cell type as MSCs [ 29 , 30 ]. BMMSCs, hDPSCs, and SHEDs, as multipotent adult stem cells isolated from different tissues, create fewer moral, ethical, or safety-related problems compared to embryonic stem cells, and are mostly investigated as a tool in regenerative medicine [ 3 , 8 , 35 , 36 , 53 ]. To date, BMMSCs, hDPSCs, and SHEDs have been demonstrated to be applicable in the treatment of various diseases, because they show immunomodulatory effects and a tissue repair ability [ 4 , 6 , 12 , 13 , 27 , 35 , 36 , 37 , 53 ].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…DPSCs secrete various growth factors and cytokines, which might be accountable for the observed outcomes in the present study. Previous studies revealed high expression levels of TGFs and neurotrophic factors, including VEGF [20,89,90]. Other factors present in the DPSC secretome involve but are not limited to IL-8, MCP-1, FGFs, MMPs, TIMP-1 [18,20,91].…”
Section: Discussionmentioning
confidence: 99%